Disorders Associated With Diverse, Recurrent Deletions and Duplications at 1q21.1 - Pang, Hui; Yu, Xiaowei; Kim, Young Mi; Wang, Xianfu; Jinkins, Jeremy K.; Yin, Jianing; Li, Shibo; Gu, Hongcang (Frontiers in Genetics, 2020)
The subchromosomal region 1q21.1 is one of the hotspots in the human genome for deletions and reciprocal duplications owing to the existence of hundreds of segmental duplications. Recurrent deletions and duplications in this region are thought to be causative in patients with variable clinical manifestations. Based on the genomic location, deletions and duplications at the 1q21.1 locus have been associated with distinguishable syndromes: chromosome 1q21.1 deletion syndrome, chromosome 1q21.1 duplication syndrome, and thrombocytopenia-absent radius (TAR) syndrome, which is partially due to deletions at the proximal 1q21.1 region. We report here the cytogenetic characterization and detailed clinical features of 36 cases with copy number variations (CNVs), including 18 patients with chromosome 1q21.1 deletions, 9 individuals carrying reciprocal duplications at 1q21.1, 2 patients with shorter deletions, and the remaining 7 individuals having variable sizes of duplications at the proximal 1q21.1 region. Notably, duplications at the proximal 1q21.1 region have not been officially associated with a defined disorder. However, more patients with proximal 1q21.1 duplications strongly suggested their causative role. Common phenotypical features of those disorders are also summarized to facilitate clinical diagnoses and genetic counseling.